Proceedings of the 17th ACM Conference on Computer Supported Cooperative Work &Amp; Social Computing 2014
DOI: 10.1145/2531602.2531605
|View full text |Cite
|
Sign up to set email alerts
|

Social media supporting political deliberation across multiple public spheres

Abstract: This paper reports on a qualitative study of social media use for political deliberation by 21 U.S. citizens. In observing people's interactions in the "sprawling public sphere" across multiple social media tools in both political and nonpolitical spaces, we found that social media supported the interactional dimensions of deliberative democracy-the interaction with media and the interaction between people. People used multiple tools through which they: were serendipitously exposed to diverse political informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
62
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 82 publications
(63 citation statements)
references
References 31 publications
0
62
0
1
Order By: Relevance
“…There is considerable discussion about how computer-mediated political discussion might serve as an online "public sphere" in the sense that Habermas [21] described it as an open forum for the rational discussion of diverse views [10,53,54], with considerable attention being paid to whether SNSs narrow or widen political discourse [3,18,28,46,74,[78][79][80][81]87]. More recently, media theorists and sociotechnical researchers have turned their attention to what has been called the "sprawling" public sphere [11] and the hybrid nature of new media [6,29,45,46].…”
Section: Social Media and Civic Participationmentioning
confidence: 99%
See 2 more Smart Citations
“…There is considerable discussion about how computer-mediated political discussion might serve as an online "public sphere" in the sense that Habermas [21] described it as an open forum for the rational discussion of diverse views [10,53,54], with considerable attention being paid to whether SNSs narrow or widen political discourse [3,18,28,46,74,[78][79][80][81]87]. More recently, media theorists and sociotechnical researchers have turned their attention to what has been called the "sprawling" public sphere [11] and the hybrid nature of new media [6,29,45,46].…”
Section: Social Media and Civic Participationmentioning
confidence: 99%
“…However, in real life people encounter information about politics in a variety of forms and utilize multiple online tools to navigate and experience political events [45,74] in what Dahlgren [11] refers to as the "sprawling" public sphere. Papacharissi [53] suggests that citizens today encounter civic society as a hybrid environment of overlapping private and public spheres and that citizenship itself is experienced in a highly fluid manner.…”
Section: Study Rationale and Research Questionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Semaan et al reported in a study of U.S. social media users' political discussions that people actively sought diverse information and discussants (Semaan et al, 2014). Some social media users changed their political views after these interactions.…”
Section: Micro-blogging For Political Deliberationmentioning
confidence: 99%
“…Researchers have accumulated a systematic body of knowledge of Western, democratic societies. Studies of the West have ranged from the deployment of novel technological systems supporting civic participation (Rheingold, 2007;Kriplean et al, 2012), to empirical studies of online and offline civic activities Semaan et al, 2014). Studies have taken place at different scales, from local communities' civic discussions (Kim et al, 2011;Parker et al, 2012) to presidential elections (Carty, 2010).…”
Section: Chapter 1 Introductionmentioning
confidence: 99%